Fear Goliath or David? Inferring Competence From Demeanor Across Cultures. (July 2020) - Lee, Albert; Ji, Li-Jun; Li, Ye; Zhang, Zhiyong
We examined cultural differences in people's lay theories of demeanor—how demeanor may be perceived as a straightforward and reliable reflection of reality (convergence theory) or as a deviating reflection of reality (divergence theory). Across different domains of competition, Euro-Canadians perceived greater competence in an opponent with a competent demeanor, whereas Chinese paradoxically perceived greater competence in an opponent with no signs of competence (Studies 1–4b). The results, unexplained by attributional styles (Study 1), likability (Study 3), or modesty (Study 3), suggest that Euro-Canadians endorse a stronger convergence theory than Chinese in their inferences of competence. Corroborated with qualitative data (Study 4a), such cultural differences were explained by the beliefs that demeanor can be a misleading reflection of reality, verified in college and community (Study 4b) samples. We discuss the implications for social perception, intergroup dynamics, and self-presentation in competitions.